Going Concern Audit Opinion: Analysis The Effect Of Financial And Non-Financial Factors - Qadarti Anjilni, Ratih; Handayani, Asih; Purwasih, Desy (Moneter: Jurnal Keuangan dan Perbankan, 2025)
Many companies are experiencing declining revenues (profitability) and disrupted liquidity due to the pressures of the Covid-19 pandemic. The impact of this decline can raise questions about the ability of companies to continue in business. For this reason, companies are required to prepare financial statements on a going concern basis, with a higher level of consideration of the Covid-19 pandemic conditions than before the Covid-19 pandemic. This study aims to test whether there is an influence of financial factors such as debt default and company growth, as well as non-financial factors: Audit tenure on the going concern audit opinion. The empirical study in this study is the real estate and property sector as a research sample in the period 2018-2022. The sample was determined using the purposive sampling method. This study was analysed using logistic regression. Logistic regression is an appropriate statistical tool for this study, as the dependent variable is dichotomous. Hypotheses were tested and conclusions were drawn based on the Hosmer and Lemeshow test, the likelihood test, the Nagelkerke R-square and the correlation and classification test. The results of the study show that financial factors proxied by the variables debt default and company growth do not affect the going concern audit opinion, but non-financial factors with the variable audit tenure affect the acceptance of the going concern audit opinion.